UX values framing: an authoring tool to capture children’s values for widening narratives - Caelenberghe, Mathias; Lochrie, Mark; Read, Janet (Interacting with computers, 2025)
Abstract This study highlights a value-led investigation into children’s (aged 9–18) views on decolonising museum experiences. The paper presents the challenges and opportunities associated with using a low-fidelity Augmented Reality authoring tool (User Experience Values Framing) to personalise museum experiences. The tool captures children’s values by employing a Value Sensitive Design approach, in addressing issues of representation, power imbalances, and cultural responsiveness in museum technologies. Through four empirical studies, the research examines the motivations behind visiting museums, value preferences, and the emergence of values amongst children. It sheds light on the effectiveness of involving children in the design process of an Augmented Reality authoring tool, highlighting their perspectives on decolonisation narratives and the desire for personalised and inclusive museum experiences. The studies highlight the importance of capturing and integrating values related to decolonisation into museum exhibition design, emphasising the needs and preferences of young audiences. Despite limitations, the insights gained offer valuable guidance for museums seeking to create more inclusive and equitable cultural exhibitions.